2011
DOI: 10.1186/1471-230x-11-35
|View full text |Cite
|
Sign up to set email alerts
|

Perforated acute appendicitis resulting from appendiceal villous adenoma presenting with small bowel obstruction: a case report

Abstract: BackgroundA villous adenoma is an extremely rare benign tumour in the appendix, in contrast to other benign appendiceal lesions. The clinical features are usually asymptomatic. Acute appendicitis is the most common complication with the lesion obstructing the orifice of the appendiceal lumen. Thus, a villous adenoma is usually found during surgical intervention for acute appendicitis. Mechanical obstruction induced by acute perforated appendicitis has been previously reported. Acute appendicitis caused by a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In elderly patients, it is more frequent to have complicated appendicitis like a periappendicular abscess, appendicular adenocarcinoma, inflammatory mass, or perforated appendicitis associated with occlusive form and bowel obstruction [ 8 ]. Perforated appendicitis increases mortality and morbidity in elderly subjects, increasing the risk of generalized peritonitis, sepsis, adhesion formation, and sometimes small bowel obstruction, which sometimes can be aggravated by personally associated comorbidities leading to severe decompensation [ 9 , 10 ]. A recent systematic review of the literature describes the incidence, form, and risk factors for perforation, mortality, and morbidity in the intestinal obstructive form of acute appendicitis (for details, see [ 9 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In elderly patients, it is more frequent to have complicated appendicitis like a periappendicular abscess, appendicular adenocarcinoma, inflammatory mass, or perforated appendicitis associated with occlusive form and bowel obstruction [ 8 ]. Perforated appendicitis increases mortality and morbidity in elderly subjects, increasing the risk of generalized peritonitis, sepsis, adhesion formation, and sometimes small bowel obstruction, which sometimes can be aggravated by personally associated comorbidities leading to severe decompensation [ 9 , 10 ]. A recent systematic review of the literature describes the incidence, form, and risk factors for perforation, mortality, and morbidity in the intestinal obstructive form of acute appendicitis (for details, see [ 9 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Concealed perforation of appendix was seen in only 1/100 (1%) patient. Chen et al [29] [34] showed that abdominal tuberculosis incidence is on the rise and is about 8.3%. Mukhopadhyay et al [11] showed that abdominal TB incidence is 10%.…”
Section: Discussionmentioning
confidence: 99%
“…The most common clinical presentation reported in the medical literature is acute appendicitis. The narrow appendiceal lumen may be occluded by the tumor early during the course and predisposes it to inflammation and perforation [ 7 , 11 , 28 ]. Other possible manifestations included a palpable abdominal mass, ascites, carcinomatosis and peritonitis resulting from a perforated appendix, and a variety of nonspecific symptoms [ 16 ].…”
Section: Discussionmentioning
confidence: 99%